2019
DOI: 10.3390/photonics6010018
|View full text |Cite
|
Sign up to set email alerts
|

Subwavelength Hexahedral Plasmonic Scatterers: History, Symmetries, and Resonant Characteristics

Abstract: In this work, we investigate the resonant characteristics of hexahedral (cubical) inclusions at the plasmonic domain. After an introduction to the notion of superquadric surfaces, i.e., surfaces that model various versions of a rounded cube, we present the main resonant spectrum and the surface distributions for two particular cases of a smooth and a sharp cube in the plasmonic domain. We present a historical comparative overview of the main contributions available since the 1970s. A new categorization scheme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Consistent with previous studies of plasmonic nanocubes, FEM field intensity maps show that the three modes observed in the spectral line shape correspond to dipolar resonances associated with the corners, edges, and faces (Figure c) , with the surface charge distribution consistent with three of the six main bright resonances that have been calculated for nanocubes (Figure S3). Mimicking the experimental measurements, the refractive index of the nanocube surroundings was systematically varied, the three optical extinction peaks were deconvoluted (Figure S4 and Table S3), and a linear fit was used to determine the theoretical RIS (Figure S5 and Table S4). For comparison, the same dielectric function was used to calculate the theoretical RIS of a nanosphere.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previous studies of plasmonic nanocubes, FEM field intensity maps show that the three modes observed in the spectral line shape correspond to dipolar resonances associated with the corners, edges, and faces (Figure c) , with the surface charge distribution consistent with three of the six main bright resonances that have been calculated for nanocubes (Figure S3). Mimicking the experimental measurements, the refractive index of the nanocube surroundings was systematically varied, the three optical extinction peaks were deconvoluted (Figure S4 and Table S3), and a linear fit was used to determine the theoretical RIS (Figure S5 and Table S4). For comparison, the same dielectric function was used to calculate the theoretical RIS of a nanosphere.…”
Section: Resultsmentioning
confidence: 99%